Testing the role of biotic stress in the stress gradient hypothesis. Processes and patterns in arid rangelands - Graff, Barbara Pamela (2011)
Since many arid ecosystems are overstocked with domestic herbivores, biotic stress could have a stronger influence in modulating the balance of species interactions than expected from the stress gradient hypothesis (SGH). Here we tested a priori predictions about the effect of grazing on species interactions and fine scale spatial structure of grasses in water‐limited ecosystems. We used detailed vegetation mapping and spatial analysis, and performed a field experiment where the direct and indirect components of positive interactions were disentangled to provide evidence of links between process and pattern. We found associational resistance (biotic refuge) to be the dominant process in grazing situations, while competition, instead of direct facilitation, seemed to govern grass spatial patterns when herbivore pressure was relaxed. These results suggest that facilitation between grasses in arid communities may be related to herbivory rather than nurse plant effects. Associational resistance tends to have the strongest effect on spatial aggregation of species at intermediate grazing pressure. Results suggest that contrary to SGH, this physical clustering of species decreased when grazing pressure reached their maximum levels. Positive associations remained significant only when palatability differences between neighbours is large, suggesting that managing stocking rate is a key factor determining the persistence of herbivory refuges. These refuges are potential foci to initiate population recovery of high quality forage species in arid degraded areas.